An adult-like pattern of ocular dominance columns in striate cortex of newborn monkeys prior to visual experience - Horton, JC (J Neurosci, 1996)
In macaque monkeys, the geniculocortical afferents serving each eye segregate in layer IVc of striate cortex during early life into a pattern of alternating inputs called ocular dominance columns. It has been disputed whether visual experience is necessary for the formation of ocular dominance columns. To settle this issue, fetal monkeys were delivered prematurely by Caesarean section at embryonic day 157 (E157), 8 d before the end of normal gestation. To avoid light exposure, the Caesarean section and all subsequent feedings and procedures were done in absolute darkness, using infrared night-vision goggles. Tritiated proline was injected into the right eye 1 d after delivery (E158). One week later at postnatal age 0 (P0), the equivalent of a full-term pregnancy (E165/P0), alternate sections of unfolded and flattened visual cortex were prepared for autoradiography or cytochrome oxidase (CO). All three newborns studied at E165/P0 had well segregated ocular dominance columns organized into the characteristic mosaic present in adults. In the upper layers, a mature pattern of CO patches (also known as blobs or puffs) was visible, aligned with the ocular dominance columns in layer IVc. Every other row of patches in layers II, III was labeled by [3H]proline. In V2, a distinct system of alternating thick- pale-thin-pale CO stripes was present. These findings indicate that stimulation of the retina by light is not necessary for the development of columnar systems in the visual cortex. Ocular dominance columns, patches, and V2 stripes all are well formed before visual experience. Even the thalamic input to the patches in the upper layers of striate cortex is segregated by eye in newborns.